Teachers’ use of digital textbooks in mathematics and science education - Helena Johansson; Anna-Karin Westman; Malin Norberg; Nina Eliasson (LUMAT)
Digital textbooks are rapidly becoming a common feature in mathematics and science teaching. At the same time, there is limited research on teachers’ use of digital textbooks for teaching. Our study takes a comparative approach, contributing to the field’s understanding of the implementation of digital textbooks in mathematics and science education. Four lower secondary teachers’ use of digital textbooks was deductively analysed concerning various features in the textbooks, using data from classroom observations and interviews with teachers and students. Results revealed similarities between teachers regardless of subject, such as using functions to guide students in the digital textbook and recognising the advantages of using videos or animations. One conclusion is that these similarities could be regarded as generic for the use of digital textbooks and important regardless of the subject. A prominent difference concerned the use of digital textbooks as a means of content processing through writing. In the mathematics classrooms, paper and pencil were used, mostly due to the limited possibility of writing mathematics in digital textbooks. In the science classrooms paper and pencil were not used, as this subject is different and to a lesser extent based on being able to represent subject content through calculations, symbols, and figures. Another difference concerns teachers’ approach to planning and tracking students’ progress, where the science teachers focus on the group and the mathematics teachers on individuals. This implies the importance of including a focus on subject-specific aspects when designing and integrating digital resources in teaching.